Role Of Contrast-Enhanced Magnetic Resonance Imaging and Diffusion- Weighted Magnetic Resonance Imaging In evaluation of the pancreatic Lesions - Ahmed Okasha; Ghada Mohamed Abd-Elrazek; Mohamed Ahmed Negm; Shimaa Mohamed Ahmed Abd-Elghani* (SVU - International Journal of Medical Sciences, 2022)
Background: Pancreatic tumor is a very lethal human tumors that needs earlier diagnosing. US, CT and MRI are various imaging methods employed to diagnose of pancreatic masses. Contrast-enhanced MRI (CE-MRI) Diffusion-weighted magnetic resonance imaging [DW-MRI] are progressively utilized or detection and characterization of various pancreatic lesions. Objectives:The current study aimed to evaluate the utility of contrast-enhanced MRI (CE-MRI) and [DW-MRI] in characterizations of pancreatic lesions. Patients and methods: This work was prospective study performed at The Department of Radiology, Qena University Hospitals, with cases with pancreatic lesions over an interval of 12 months who previously discovered by other imaging modalities that desire more characterizations via MRI. Results: The DWI imaging sensitivity was 100%, specificity was 100%, NPV was 100% and PPV was 100% with accuracy of 100% for detecting benign and malignant tumors.ADC value was significant at cutoff value . Conclusion: We concluded that CE-MRI and DW-MRI is a reliable screening and diagnosing method for characterization of pancreatic lesions.